'Not my dream': Mother's challenge of raising intellectual disability child in Vhembe district - Ndidzulafhi S. Raliphaswa; Mary Maluleke; Mutshinyalo L. Netshikweta (AOSIS, 2022)
Background: The birth of a child with an intellectual disability in a family brings confusion, depression and frustrations, especially to the mother. Activities required by these children place a heavy burden on mothers in terms of support and care, as most mothers are the ones who take full care in the well-being of a child, regardless of whether a child has an intellectual disability or not. Challenges include feeding, bathing, dressing, finance and assisting with elimination, especially when the child is a teenager, where one expects the child to be able to do everything for himself or herself. Aim: To explore and describe the challenges experienced by mothers of children with intellectual disabilities. Setting: The study was conducted in the selected hospitals of the Vhembe district in Limpopo province. Methods: A qualitative, exploratory, descriptive and contextual research design was adopted. A nonprobability purposive sample comprised 13 mothers of children with intellectual disabilities such as down syndrome and cerebral palsy. Data were collected through unstructured interviews until saturation was reached. Data were analysed by the open-coding method. Results: Study findings revealed that mothers of children with intellectual disabilities experienced feelings of fear, embarrassment and financial burdens because of children's special needs and initial awareness of the diagnosis. Conclusion: It is imperative that mothers of children with intellectual disabilities be supported by family, relatives, health care professionals and the community. Contribution: The study's contribution was to strengthen psychological intervention and support to mothers and awareness to accept children with intellectual disability.